INTEGRASI PENDIDIKAN NILAI DALAMPEMBELAJARAN PKN UNTUK MEMBENTUK PROFIL PELAJAR PANCASILA DI ERA DIGITAL: SEBUAH STUDI LITERATUR SISTEMATIS - Yakobus Ndona; Sri Hartati; Daulat Saragi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The digital era has changed education, and there is now a need for new ways to teach Pancasila values. Civic Education (PKn) is an important subject that must find ways to connect these values to students' lives in today's digital world. This study looks at effective methods for incorporating values education into PKn learning. The goal was to develop a Pancasila Student Profile in the digital era by reviewing 25 accredited journal articles. The findings revealed three effective strategies: using digital technology with interactive learning media, applying constructivist and project-based learning methods, and improving teachers' roles as digital role models. Implementing these strategies significantly helped instill the values of tolerance (72%), responsibility (68%), and digital skills (75%) in students. The study concluded that successfully integrating values education into PKn in the digital era requires a thorough approach. This approach needs to blend Pancasila value content, innovative teaching methods, and smart use of technology, with success relying on teacher readiness and support from the digital educational environment.